IFPRI-Bangladesh "Food Security in Bangladesh: What Role for Social Safety Nets?" - Ahmed, Akhter (2018)
Using data from IFPRI's Bangladesh Integrated Household Survey (BIHS) and secondary data, IFPRI Country Representative Dr. Akhter Ahmed presents results on poverty, agricultural production, nutrition, and policy conclusions.